PEMBUATAN ES KRIM FUNGSIONAL DENGAN BAHAN BAKU SOYGHURT DAN SUSU RENDAH LEMAK - Eka Saputri; Evy Rossi; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to obtain the ratio of soyghurt and low fat milk in produce a functional ice cream with best of a value overrun, melting point, total lactic acid bacteria (LAB), and total solids. This research used a Completely Randomized Design (CRD) with four treatments and four replications. The treatments were SSr1 (soyghurt 100 : 0 low fat milk), SSr2 (soyghurt 80 : 20 low fat milk), SSr3 (soyghurt 60 : 40 low fat milk), and SSr4 (soyghurt 40 : 60 low fat milk). The data obtained were analyzed statistically by using Analysis of Variance (ANOVA). If the F count was greater than or equal to F table then continued with DNMRT test at 5% level. The results of this research showed that the ratio of soyghurt and low fat milk in produce functional ice cream indicated significant effect (P<0,05) on overrun value, melting point, total LAB, and total solids. The treatment SSr4 having overrun value of 35.98%, melting point 20.14 minutes, total LAB 8.77 log CFU/ml, pH 5.24, and total solids 26.80% was relatively better than other treatments. The functional ice cream obtained from SSr4 was also preferred by panelists than other treatments especially for hedonic acceptance test. Keywords: Soyghurt, low fat milk, functional ice cream